Efficacy of Chinese Herbal Medicine in the Treatment of Moderate-Severe Painful Diabetic Peripheral Neuropathy: A Retrospective Study - Yujiao Zheng; Fan Yang; Lin Han; Xiaowen Gou; Fengmei Lian; Wenke Liu; Linhua Zhao; Bing Pang; Xiyan Zhao; Xiaolin Tong (Journal of Diabetes Research)
Painful diabetic peripheral neuropathy (pDPN) is a debilitating complication of diabetes. The aim of this retrospective study was to investigate the effectiveness of a Chinese herbal medicine regimen—the modified Huangqi Guizhi Wuwu Decoction (HGWD)—in the treatment of moderate-severe pDPN. The primary objective was to estimate the improvement in neuropathic pain severity. The secondary objective was to assess the response of common symptoms to the treatment. The change in patients’ blood glucose level during the whole treatment was also evaluated. By searching through our medical records of all the diabetic patients from January 2006 to January 2012, we identified and enrolled 30 moderate and severe pDPN patients in the study, for whom the treatment of neuropathic pain by regular pharmacotherapies had failed. The modified HGWD treatment was administered orally twice a day for 6 months. The numerical rating scale (NRS) level at month 6 was 2.57±2.30, significantly improved compared with the baseline level of 6.03±1.83 (P<0.05). The amelioration of 3 common symptoms, namely, limb pain, limb numbness, and insomnia, was evident, and the major response of common symptoms at month 6 including limb pain, insomnia, and limb coldness was significantly increased compared with the results at month 3 (P<0.05). Moreover, 2-hour postprandial blood glucose (2hPG) level decreased from 10.77±1.29 mmol/L at baseline to 9.66±0.60 mmol/L at month 6 (P<0.05). No serious adverse events occurred throughout the treatment period. The modified HGWD was effective in the treatment of moderate and severe pDPN and can thus be offered as a new alternative treatment option for pDPN patients who failed to respond to regular pharmaceutical therapies.